The Comparison of Online Sale and Purchase Agreements as an Effect of Globalization in Indonesia & Malaysia - Soetoto, Erwin Owan Hermansyah (International Journal of Law Reconstruction, 2024)
The regulations on online buying and selling as an effort to adapt to the development of the global digital economy. Although Indonesia and Malaysia are in the same region, they have different legal approaches applied in online buying and selling agreements. The purpose of this study is to analyze the regulation of online buying and selling agreements in Indonesia and Malaysia, as well as to analyze the ideal regulation of online buying and selling agreements in Indonesia in the future. The approach method in this study uses a normative legal approach. The results of this study are that Indonesia can adopt security in transactions applied in Malaysia by using electronic signatures as a mandatory component in online buying and selling transactions. In the future, regulations regarding electronic signatures will be strengthened by requiring their use in online buying and selling transactions. With the obligation to use digital signatures, each party involved in the transaction will have a verified identity. This will reduce the risk of fraud and data manipulation in online buying and selling transactions.